Fabrication of Waterproof Artificial Compound Eyes with Variable Field of View Based on the Bioinspiration from Natural Hierarchical Micro–Nanostructures - Zhou, Peilin; Yu, Haibo; Zhong, Ya; Zou, Wuhao; Wang, Zhidong; Liu, Lianqing (Nano-Micro Letters, 2020)
Planar and curved microlens arrays (MLAs) are the key components of miniaturized microoptical systems. In order to meet the requirements for advanced and multipurpose applications in microoptical field, a simple manufacturing method is urgently required for fabricating MLAs with unique properties, such as waterproofness and variable field-of-view (FOV) imaging. Such properties are beneficial for the production of advanced artificial compound eyes for the significant applications in complex microcavity environments with high humidity, for instance, miniature medical endoscopy. However, the simple and effective fabrication of advanced artificial compound eyes still presents significant challenges. In this paper, bioinspired by the natural superhydrophobic surface of lotus leaf, we propose a novel method for the fabrication of waterproof artificial compound eyes. Electrohydrodynamic jet printing was used to fabricate hierarchical MLAs and nanolens arrays (NLAs) on polydimethylsiloxane film. The flexible film of MLAs hybridized with NLAs exhibited excellent superhydrophobic property with a water contact angle of 158°. The MLAs film was deformed using a microfluidics chip to create artificial compound eyes with variable FOV, which ranged from 0° to 160°. Highlights: 1 Bioinspired by natural superhydrophobic surface with hierarchical micro–nanostructures, waterproof artificial compound eyes with variable field of view (FOV) were fabricated by a simple and effective manufacturing method. 2 The fabricated artificial compound eyes exhibited excellent waterproof property, tunability of the FOV and optical performance.